Nivolumab and Hypofractionated Radiotherapy in Patients With Advanced Lung Cancer: ABSCOPAL-1 Clinical Trial - Ye, Hua; Pang, Haowen; Shi, Xiangxiang; Ren, Peirong; Huang, Shangke; Yu, Hong; Wu, Jingbo; Lin, Sheng (Frontiers in Oncology, 2021)
Background More clinical practice need to be performed to verify the toxicity of the hypofractionated radiotherapy (HFRT) combined with PD-1 blockade in lung cancer. This phase I study aimed to investigate the safety and efficacy of nivolumab combined with HFRT in patients with progressive advanced lung cancer following multiline treatment. Methods We enrolled 31 patients with advanced lung cancer pathologically confirmed to have progressive disease and treated with first-line or a higher therapy. Selected lesions were treated using HFRT, and nivolumab was administered within 7 days subsequently. Nivolumab was administered once a month following partial remission. Peripheral blood was collected before and after 1 month of treatment to evaluate relevant cytokines between nivolumab responders and non-responders. Results Overall, 23 patients who completed the treatment were evaluated. Of them, 9 and 14 patients underwent hypofractionated brachytherapy with 30 Gy in a single fraction via percutaneous interstitial implantation of (192)Ir and 40–50 Gy in 5 fractions via stereotactic body radiation therapy, respectively. The median follow-up period was 11 months. At the 1-year follow-up, no patient developed grade ≥ 3 pneumonitis. The overall objective response and complete remission rates were 39.13% and 13.04%, respectively. The 1-year overall survival and median progression-free survival were 60.9% and 6 months, respectively. The plasma levels of interleukin IL-6, IL-10, and IL-17A were significantly reduced after treatment in nivolumab responders. Conclusions HFRT could increase the responsivity to nivolumab and reduce its administration frequency. This combination treatment is well tolerated with acceptable toxicity and thus merits further trials to validate benefits. Clinical Trial Registration http://www.chictr.org.cn/index.aspx, identifier ChiCTR-1900027768.